Social limits to redistribution and conspicuous norms - Luca Ferrari (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In this article the author considers an economy in which individuals are matched into pairs and the desirability of an individual depends on her position on the distribution of wealth. He assumes that individuals show their relative standing by consuming a conspicuous good and he shows that there exist different social norms supporting different matching arrangements. In addition, individuals have to vote over a redistributive policy and the author shows that, despite the desirability of the full redistributive outcomes, under some economic conditions the medium class is able to match with the high class in exchange of a minimum level of redistribution of wealth which keeps the low class far from economic and social opportunities.
Keywords: D11; D31; D62; 330; social status; conspicuous consumption; matching; redistribution of wealth; income inequality; social organizations